Rasio Monosit LDL Cholesterol dan Neutrofil LDL Cholesterol pada Penderita TB - Agraini, Agraini; Muslina, Muslina; Lestari, Uce; Elisma, Elisma; Saquro, Abdan (Journal of Telenursing (JOTING), 2024)
This study analyzes the relationship between monocyte LDL cholesterol and LDL neutrophil values ​​in patients with pulmonary TB. The research method used is descriptive observational analytic with a cross-sectional study design. The results of the study showed that monocyte values ​​with LDL cholesterol showed a p-value> 0.05 with an r value = 110 so it can be concluded that there is no significant relationship between monocyte values ​​and LDL cholesterol levels in patients with pulmonary TB. The results of the Pearson statistical test of neutrophil values ​​with LDL cholesterol levels showed a p-value> 0.05 with an r value = -0.134. In conclusion, there is no relationship between monocyte LDL cholesterol and LDL neutrophil values ​​in patients with pulmonary TB. Keywords: Cholesterol, LDL, Monocytes, Neutrophils, TB